2009
DOI: 10.1097/gim.0b013e318193ba67
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Fanconi anemia complementation Group A assignment using molecular analysis

Abstract: Purpose: Fanconi anemia is a genetically heterogeneous chromosomal breakage disorder exhibiting a high degree of clinical variability. Clinical diagnoses are confirmed by testing patient cells for increased sensitivity to crosslinking agents. Fanconi anemia complementation group assignment, essential for efficient molecular diagnosis of the disease, had not been validated for clinical application before this study. The purpose of this study was (1) confirmation of the accuracy of Fanconi anemia complementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…For the majority of patients, FA is suspected only after the onset of pancytopenia. Genetic studies in FA-A patients of various ethnic groups have revealed a variety of mutations, including large deletions, nucleotide substitutions, and small deletions/insertions across the entire gene without a mutation-clustered region (15,16). A precise diagnosis can be made with careful history, physical examination, and a positive chromosomal breakage test in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of patients, FA is suspected only after the onset of pancytopenia. Genetic studies in FA-A patients of various ethnic groups have revealed a variety of mutations, including large deletions, nucleotide substitutions, and small deletions/insertions across the entire gene without a mutation-clustered region (15,16). A precise diagnosis can be made with careful history, physical examination, and a positive chromosomal breakage test in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…All living affected individuals were specifically screened for all of the major IBMFS; genotyping was performed when possible (Ameziane et al , 2008; Moghrabi et al , 2009). Affected individuals who had not received a transplant had bone marrow aspirations, biopsies and cytogenetic studies.…”
Section: Methodsmentioning
confidence: 99%
“…Other congenital abnormalities include congenital hip dislocation, scoliosis with vertebral anomalies, cafe´au lait spots (63-79%), low birth weight, microphthalmia, microcephal, renal anomalies (30%) (especially renal agenesis and renal ectopia), microcephaly, hypogenitalia (51%) with hypoplastic gonads, small uterus in females and hypospadias in males, gastrointestinal anomalies (including esophageal atresia, duodenal atresia and imperforate anus), congenital heart disease (especially patent ductus arteriosus), ventricular septal defect, pulmonic valvar stenosis and coarctation. 6,7 The concurrence of VACTERL features has been described in FANC A, C, D1, F and G. 4 VACTERL-H syndrome, which is an X-linked condition with hydrocephalus, usually aqueductal stenosis, has been associated with FANC B.…”
Section: Denouement and Discussionmentioning
confidence: 99%
“…4,5 Radial ray anomalies occur in 63-79% of patients, especially anomalies of the thumb (49-66%). Other congenital abnormalities include congenital hip dislocation, scoliosis with vertebral anomalies, cafe´au lait spots (63-79%), low birth weight, microphthalmia, microcephal, renal anomalies (30%) (especially renal agenesis and renal ectopia), microcephaly, hypogenitalia (51%) with hypoplastic gonads, small uterus in females and hypospadias in males, gastrointestinal anomalies (including esophageal atresia, duodenal atresia and imperforate anus), congenital heart disease (especially patent ductus arteriosus), ventricular septal defect, pulmonic valvar stenosis and coarctation.…”
Section: Denouement and Discussionmentioning
confidence: 99%
See 1 more Smart Citation